An Evidence-Based Review on Shirodhara: A Unique Panchakarma Therapy (International Journal of Ayurveda and Pharma Research, 2022)
Shirodhara is a procedure consisting of continuous pouring of a stream of medicated oil, milk, buttermilk, etc. on the forehead of the patient from a specific height for a specified period. Acharya Vagbhatta has described four types of Murdha Tail i.e., Abhyanga, Parishek, Pichu, and Shirobasti, which is successively more beneficial than the previous one. Shirodhara or Shiroparishechan is one of them. Indication of Shirodhara was found in our ancient textbooks in various diseases like Ardhavabhedaka, Suryavarta, Ardita, Pakshaghata, Hanugraha, Akshishula, Nidranasha, Shirogata Vata and Shirahkampa.In the modern era, it is a very widely used Panchakarma therapy and in this review article, an evidence-based approach is used to define the type, procedure, indication contraindication, mode of action, complications and management and evidence of efficacy etc. of Shirodhara. Based on evidence Shirodhara has been found effective in various disorders like Insomnia, Psoriasis, ADHD in children, Shirah Shoola, essential hypertension, cerebral ischemic stroke and premature ejaculation when accompanied with other treatment modalities. Shirodhara was found effective on subjective as well as scientific parameters or modern biochemical markers parameters in various studies.